2016
DOI: 10.1080/00087114.2016.1224402
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of the cytogenetics of the genusPhlomoides(Lamiaceae) in Iran

Abstract: The present study reports the chromosome number and meiotic behavior of 11 populations belonging to four species of Phlomoides (L.) Moench. All populations showed the diploid chromosome number 2n = 2x = 22; consistent with the proposed base number of x = 11. Almost all taxa studied here displayed regular bivalent pairing and chromosome segregation at meiosis. However, meiotic abnormalities observed included varied degree of fragmented chromosomes, laggards and bridge in anaphase I to telophase II, precocious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Azizian and Cutler (1982) stated that polyploid was not so common in the genus Eremostachys (Phlomoides) suggesting a base number of x=11. Based on the published chromosome counts (2n=12, 14, 21, 20, 22, 24, 28, 42, 46, and 88) available for the species of genus Phlomoides and 2n=22 the most represented count in the genus, Ranjbar et al (2016) also suggested x=11 as the basic number for the genus. In acceptance with the previous reports and the current report, it can be said that the P. superba occurs at diploid level (2x) in its entire range from Afghanistan to Uttar Pradesh in India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azizian and Cutler (1982) stated that polyploid was not so common in the genus Eremostachys (Phlomoides) suggesting a base number of x=11. Based on the published chromosome counts (2n=12, 14, 21, 20, 22, 24, 28, 42, 46, and 88) available for the species of genus Phlomoides and 2n=22 the most represented count in the genus, Ranjbar et al (2016) also suggested x=11 as the basic number for the genus. In acceptance with the previous reports and the current report, it can be said that the P. superba occurs at diploid level (2x) in its entire range from Afghanistan to Uttar Pradesh in India.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent deviation from normal meiotic behavior in the currently studied species is out of plate bivalents and early disjunction which can be due to spindle abnormalities. The chromatids/chromosomes are attached to the spindles with kinetochores which help to keep it in the desired orientation for uniform distribution of chromosomes at the poles (Ranjbar et al 2016). Normally bipolar spindle is responsible for this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on taxonomy, molecular phylogeny of Phlomoides species can be seen in the works of Salmaki [3], Ranjbar [4], Komarevseva [5], Gulomov [6].…”
Section: Introductionmentioning
confidence: 99%